Amílcar Cabral : A Nationalist and Pan-Africanist Revolutionary - Mendy, Peter Michael Karibe (Book collections on Project MUSE., 2019)
Amílcar Cabral's charismatic and visionary leadership, his pan-Africanist solidarity and internationalist commitment to ""every just cause in the world,"" remain relevant to contemporary struggles for emancipation and self-determination. This concise biography is an ideal introduction to his life and legacy.